Penerapan Situational Communication Crisis Theory bagi Organisasi Dakwah dalam Menghadapi Situasi Krisis - Rizky Saputra (Universitas Medan Area, 2020)
This paper will discuss a theory in dealing with a crisis situation in the context of a da'wah organization in general, which of course will be different from the crisis context of a business company, both in terms of the type of issue or problem to the handling of the crisis situation. According to Coombs, there are five message strategies that are usually used in crisis communication, namely: (1) Non-existence strategies. This strategy is carried out by organizations that are not experiencing a crisis, but there are rumors that the organization is facing a crisis; (2) Distance strategies. Organizations that acknowledge a crisis are used and try to weaken the relationship between the organization and the crisis that has occurred; (3) Ingratiation strategies. This strategy is used by organizations in seeking public support; (4) Mortification strategies. The organization tries to apologize and accept the fact that there is a real crisis; (5) Suffering strategies. Organizations also show suffering as victims of those who are not happy with the organization and seek to gain public support and sympathy. The choice of crisis communication strategy must be considered by the da'wah organization that will carry out its crisis communication by still considering the situation, type of problem, and the scale or size of a crisis that occurs as well as the organization's ability to reach the choice of communication model.